Lebanon : Electricity Sector Public Expenditure Review - World Bank (Washington, DC, 2012)
The Lebanese electricity sector is at the heart of a deep crisis. The sector is unable to supply the reliable electricity needed by homes, offices and industry. It is a massive drain on government finances, crowding out more valuable expenditures on education, infrastructure, social protection, and health, and putting macroeconomic stability at risk. The sector accumulates huge debt with little to show for it, and those who are least able to provide for themselves suffer the consequences most. The state of the electricity sector symbolizes to the public Lebanon's profound challenges of governance, inclusion and accountability. This report includes detailed calculations on these estimated high costs to the public. This additional spending and revenue loss has an obvious negative impact on these consumer categories, but also makes implementation of other macro-critical, non electricity sector reforms, difficult; as consumers have difficulty absorbing increased overall spending (for example tax increases). As such, this report presents an analysis of possible demand and supply scenarios for the future, and lays out options for the Government to consider in improving service and reducing the overall costs. Each option is presented with a savings potential, and time-line for implementation. Ultimately, however, the Government will have to consider how to sequence the reforms, in particular, the invariable tension between waiting with the much needed tariff level and structure adjustments for an observable improvement in service delivery versus starting the adjustments immediately and working on service improvements in parallel.